Ionic liquid gel polymer electrolytes for flexible supercapacitors: Challenges and prospects - Jamil, Rabia; Silvester-Dean, Debbie (2022)
Ionic liquid gel polymer electrolytes (IL-GPEs) have attracted wide interest in the field of electrochemical energy storage devices, particularly for their use in flexible supercapacitors (FSCs). IL-GPEs integrate ionic liquids (ILs) as either a solvent or as a polymerizable unit. They possess several attractive properties including high ionic conductivity, wide operating potential range, good thermal stability, tunable chemical functionalities and self-healing capabilities. In this short review, an overview of IL-GPEs is provided, first describing their classification, fundamental properties, and chemical design, then detailing some of the most recent essential advances in the field along with their limitations.